A família como campo de atuação e investigação do serviço social brasileiro - Vignoli, Maria Francisca Sales (2007)
The present dissertation concerns about the current transformation of families regarded in the theoretical production of the brazilian social service. It is about a historical bibliographer research, accomplisher through the survey of some classic references which approach this subject but mainly through the renowned social service & Society magazines which have brought the word family as title. We have aimed at the acquaintance of theoretical contributions of the brazilian social assistants about the thematic above mentioned and aimed at the widening of our own knowledge as professionals who directly act on those mentioned users, as well. This essay has intended to point out the inquiries that have been outlined during the procedure of the study as well as requires closed to the mainly issue. We have been in need to pursuit an extended understanding of family, which certainly is a social institution, questioning its complexity and its contradictions. It has been realized that family has to be regarded in all of its present configurations and in its imputed responsibilities as well. In order to understand what have been happening in a contemporaneous way, this research started from the antiquity with goal of getting to know the conception of those families in some countries and, mainly, to understand the transformations that took place in those families from Brazil. It has been also studied the brazilian social politics and some historical facts of the government lead by Getúlio Vargas and Luis Inácio Lula da Silva (From 1930 to 2006). It has been concerned, as well, the social politics turned on families, their relations with the state in the past few decades, giving priority to the social claims, to the social service and to the social assistants actuation in regard to the mentioned requirements. This study has helped us in the widening of our knowledge about this thematic, which has allowed us to face the challenges that require professional intervention